Influence of Calcined Diatoms on the Properties of Conventional Concrete - Pejerrey Barreto, Eduardo; Sanchez Bautista, Juan Jacobo (International Journal of Sustainable Construction Engineering and Technology, 2024)
Today, the construction industry has expressed its preference for the use of sustainable materials due tothe significant impact they have on the environment. Although concrete is widely used in construction due to itsdiverse properties, one of its main components, known as clinker, is a major contributor to CO2 pollution. Therefore,the feasibility of partially replacing this material with alternatives is being investigated. Among them, calcineddiatoms are presented as a promising option. These are an extremely fine and highly porous material, composedmainly of silica, which has a large specific surface area. The abundant presence of active silica improves theproperties of concrete, such as its strength, while the ultrafine particles of diatoms densify the concrete structure,thus achieving a concrete with greater durability. The objective of this study was to evaluate the properties ofconventional concrete, both fresh and hardened, by adding calcined diatomite in proportions of 5%, 10% and 15%,with the purpose of determining the optimum percentage of calcined diatomite to achieve adequate concretedevelopment. Test specimens were elaborated without the addition of calcined diatoms and with the addition ofcalcined diatoms, then immersed in water for 7d, 14d and 28d. Tests were carried out in the fresh state to obtainworkability, bleeding, setting time, air content, temperature, and unit weight. In the hardened state, tests were carriedout to obtain compressive strength, static modulus of elasticity and permeability. It was found that with a loweraddition of calcined diatomaceous earth, the concrete can develop as a normal concrete, and improvements incompression were obtained, increasing with respect to the control concrete. However, by increasing the percentageof calcined diatomite, the workability is reduced and in general, the properties do not show an improvement. Concretewith the addition of calcined diatomite can be used as a thermal insulator, since it presents very fine particles thatperform a filling effect, densifying the concrete matrix, and it can also be used for lightweight concrete since itreduces 17kg/m3. On the other hand, the compressive strength with 5% calcined diatomite increased by 9% withrespect to the standard, due to its high pozzolanic activity. In addition, a lower permeability was found with theaddition of 5% calcined diatomite. In general, calcined diatomite in lower proportions can generate resistant anddurable concrete.